Response Mode Choice in a Multimodally Duetting Paleotropical Pseudophylline Bushcricket - Rajaraman, Kaveri; Nair, Aswathy; Dey, Anjana; Balakrishnan, Rohini (Frontiers in Ecology and Evolution, 2018)
Females of the pseudophylline bushcricket species Onomarchus uninotatus respond to a conspecific acoustic call with bouts of tremulation, followed by phonotaxis in some cases. This tremulation sends out a vibratory signal that propagates along the branch of the jackfruit trees where these animals are almost always found, and the male is able to localise the signal and perform vibrotaxis towards the female. Males are unable to localise the signal if it emanates from a branch unconnected to their perch, and therefore, female tremulation might not be a productive response when the nearest male is on an adjacent, disconnected tree. We hypothesised that female behavioural response choice between tremulation and phonotaxis might vary with distance from the caller. A semi-naturalistic experiment indicates that if the male and female are 4 m apart on a connected perch, females tremulate and never perform phonotaxis while males perform vibrotaxis. However, at a distance of 9 m, 4 out of 10 females begin phonotaxis after a period of tremulation. We then hypothesized that features of the male call that indicate caller distance, such as call sound pressure level (SPL), might be responsible for this distance-dependent variation in the choice between phonotaxis and tremulation However we found that at all SPLs, the female tremulates in response to male calls before attempting phonotaxis and that the probability of phonotaxis and tremulation both increased with calling song SPL. We conclude that our first hypothesis is upheld and that females do behave differently with respect to distance from the male, but that the cue affecting the distance-dependent increase in the probability of initiation of phonotaxis in female response choice is not the SPL of the male’s advertisement call.